A Tandem Interfaced (Ni3S2‐MoS2)@TiO2 Composite Fabricated by Atomic Layer Deposition as Efficient HER Electrocatalyst. Issue 24 (12th May 2022) - Guo, Daying; Wan, Zhixin; Fang, Guoyong; Zhu, Mengqi; Xi, Bin
Abstract: Reported herein is a highly active and durable hydrogen evolution reaction (HER) electrocatalyst, which is constructed following a tandem interface strategy and functional in alkaline and even neutral medium (pH ≈ 7). The ternary composite material, consisting of conductive nickel foam (NF) substrate, Ni3 S2 ‐MoS2 heterostructure, and TiO2 coating, is synthesized by the hydrothermal method and atomic layer deposition (ALD) technique. Representative results include: (1) versatile characterizations confirm the proposed composite structure and strong electronic interactions among comprised sulfide and oxide species; (2) the material outperforms commercial Pt/C by recording an overpotential of 115 mV and a Tafel slope of 67 mV dec −1 under neutral conditions. A long‐term stability in alkaline electrolytes up to 200 h and impressive overall water splitting behavior (1.56 V @ 10 mA cm −2 ) are documented; (3) implementation of ALD oxide tandem layer is crucial to realize the design concept with superior HER performance by modulating a variety of heterointerface and intermediates electronic structure. Abstract : Based on the multilevel design with the interfaces tandem, the excellent catalytic activity, long‐term stability, and universality of the hydrogen evolution reaction under the alkaline and neutral conditions are achieved.